2020
DOI: 10.1097/phh.0000000000001152
|View full text |Cite
|
Sign up to set email alerts
|

Needling Policy Makers and Sharpening the Debate: Do Syringe Exchange Programs Improve Health at the Population Level?

Abstract: Context: In the midst of the current opioid epidemic, states have selected differing legislative routes implementing pathways to ensure access to clean needles and syringes. Objective: To determine whether states that implemented laws supporting syringe exchange programs (SEPs) had reductions in transmission rates of hepatitis B, hepatitis C, and HIV infection compared with states without such laws. Design and Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…HIV/HCV/STI testing, sterile syringe and injection equipment distribution, naloxone distribution, etc.) is a vital part of reducing the burden of drug‐use related pathology, and should be highly considered in the setting of continued injection drug use 4,5,51 . The absence of harm reduction discussion in the cardiac surgery literature therefore, highlights an educational gap among physicians, and is an important area of improvement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV/HCV/STI testing, sterile syringe and injection equipment distribution, naloxone distribution, etc.) is a vital part of reducing the burden of drug‐use related pathology, and should be highly considered in the setting of continued injection drug use 4,5,51 . The absence of harm reduction discussion in the cardiac surgery literature therefore, highlights an educational gap among physicians, and is an important area of improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, people who use drugs (PWUD) are a marginalized social group who are heavily impacted by the nature of the current crisis. In terms of healthcare, PWUD have poorer health outcomes largely due to psychosocial factors like poverty and institutional barriers to equitable medical care like poor access to specialty physicians 5,6 . Specifically, past studies have demonstrated that PWUD have greater mortality and rates of infection reoccurrence and postprocedural complications compared to non‐PWUD 7 .…”
Section: Introductionmentioning
confidence: 99%
“…On a state-by-state level, there is evidence for NEP reduces HCV incidence. However, as access improves across the USA, this intervention's effect would need further analysis of its case and cost burden alongside a comparison against DAA or NEP with DAA solutions to optimize a solution to reported disproportionate cost burdens [48].…”
Section: Discussionmentioning
confidence: 99%
“…From an implementation perspective, some activities for tackling OUD and adverse outcomes are likely more challenging and may require greater resources and political and planning commitment than others. For example, needle exchange programs have long been a source of political controversy 38 despite evidence that such programs are generally safe, economical, and effective, 39 and reduce rates of viruses at the population level related to OUD such as hepatitis B and hepatitis C. 40 Establishing needle exchanges may thus be more politically or legally challenging for some policy makers than a less contentious harm reduction activity such as having police carry naloxone while on duty.…”
Section: Discussionmentioning
confidence: 99%